Genetic basis of elite combat sports athletes: a systematic review - Youn, B.; Ko, S.; Young Kim, J. (Biology of Sport, 2021)
Each athlete`s innate talent is widely recognized as one of the important contributors to achievement in athletic performance, and genetic factors determine a significant portion of talent or traits. Advances in DNA sequencing technology allow us to discover specific genetic variants contributing to these traits in sports performance. The objective of this systematic review is to identify genes that may play a significant role in the performance of elite-level combat sports athletes. Through the review of 18 full-text articles, a total of 109 different polymorphisms were investigated in 14,313 participants (2,786 combat sports athletes, 8,969 non-athlete controls, 2,558 other sports athletes). Thirteen polymorphisms showed a significant difference between elite combat athletes and the control group, and consist of 8 (PPARA rs4253778, ACTN3 rs1815739, ACE rs4646994, CKM rs8111989, MCT1 rs1049434, FTO rs9939609, GABPß1 rs7181866 and rs8031031) oriented to athletic performance and 5 (COMT rs4680, FEV rs860573, SLC6A2 rs2242446, HTR1B rs11568817, ADRA2A rs521674) focused on psychological traits including emotional and mental traits in combat sports athletes. In addition, a recent whole genome sequencing study identified 4 polymorphisms (KIF27 rs10125715, APC rs518013, TMEM229A rs7783359, LRRN3 rs80054135) associated with reaction time in wrestlers. However, it is not clearly identified which genes are linked explicitly with elite combat sports athletes and how they affect the elite athlete`s status or performance in combat sports. Hence, a greater number of candidate genes should be included in future studies to practically utilize the genetic information.